CD155 as a therapeutic target in alveolar echinococcosis: insights from an Echinococcus multilocularis infection mouse model - Zhang, Xue; Li, Liang; Sun, Tao; Yang, Ning; Liu, Hui; Chu, Jin; Xue, Junlong; Lü, Guodong; Aji, Tuerganaili; Bi, Xiaojuan; Lin, Renyong (Frontiers in Microbiology, 2025)
IntroductionAlveolar echinococcosis (AE) is a life-threatening zoonotic parasitic disease caused by the metacestode stage of Echinococcus multilocularis, characterized by granulomatous lesions and liver fibrosis. Immune exhaustion is the key mechanism by which E. multilocularis evades host immune responses and maintains long-term parasitism. Although CD155 is recognized as an immune checkpoint molecule, its specific role and underlying mechanism in AE remain unclear.MethodsA mouse model of E. multilocularis infection was used to investigate the role of CD155 in AE progression. Flow cytometry, immunohistochemistry, and immunofluorescence were employed to assess CD155 expression and analyze T-cell function. In addition, liver weight, lesion size, lesion number, inflammation index, collagen deposition (via Masson staining), and stellate cell activation (via α-SMA immunohistochemistry) were statistically quantified in the CD155 hepatocyte knockout mice. Each experimental group included five mice (n = 5).ResultsCD155 expression in hepatocytes was significantly increased—approximately 2-fold compared to Sham controls—and predominantly localized near lesion sites. The infected group showed significantly reduced percentages of functional CD4+IFN-γ+, CD4+CD107a+, and CD8+CD107a+ T cells (p < 0.05), along with enrichment of exhausted TIGIT+ T cells adjacent to CD155+ hepatocytes. In vitro, CD155 expression in hepatocytes was upregulated in a dose-dependent manner when co-cultured with metacestode vesicles, reaching 1.5-fold that of the control. Notably, hepatocyte-specific CD155 knockout in infected mice restored CD4+ and CD8+ T-cell function and reduced liver damage, as indicated by decreased lesion burden.ConclusionIn the E. multilocularis infection mouse model, excretory/secretory products from metacestode vesicles upregulated CD155 expression in hepatocytes, contributing to an immunosuppressive microenvironment and T-cell exhaustion. Targeting CD155 reverses this immunosuppression and mitigates hepatic pathology, highlighting CD155 as a promising therapeutic target for AE.